2017
DOI: 10.1039/c7dt90127e
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Infrared nonlinear optical properties of lithium-containing diamond-like semiconductors Li2ZnGeSe4 and Li2ZnSnSe4

Abstract: Correction for ‘Infrared nonlinear optical properties of lithium-containing diamond-like semiconductors Li2ZnGeSe4 and Li2ZnSnSe4’ by Jian-Han Zhang et al., Dalton Trans., 2015, 44, 11212–11222.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…The blueshift of the long‐wavelength EQE edge correlates with the bandgap increase that is proportional to the lithium fraction. This trend is analogous to what Lafond et al reported and it is expected as the bandgap of Li 2 ZnSnSe 4 phase is of 2.0 eV …”
Section: Resultssupporting
confidence: 89%
“…The blueshift of the long‐wavelength EQE edge correlates with the bandgap increase that is proportional to the lithium fraction. This trend is analogous to what Lafond et al reported and it is expected as the bandgap of Li 2 ZnSnSe 4 phase is of 2.0 eV …”
Section: Resultssupporting
confidence: 89%
“…Any thermal load on the samples by the laser pulses tuned below the bandgap was negligible because of its slow repetition rate of 50 Hz. The details regarding the excitation source are available elsewhere. , …”
Section: Experimental Sectionmentioning
confidence: 99%
“…[ 6 ] Among them, selenides normally exhibit wider IR transparent regions, larger SHG responses, and lower melting points, but smaller band gaps than sulfides. [ 7 ] Over the past decades, a plenty of selenides with good NLO properties like LiGaSe 2 , [ 8 ] α ‐BaGa 4 Se 7 , [ 9 ] β ‐BaGa 4 Se 7 , [ 10 ] β ‐BaGa 2 Se 4 , [ 11 ] Li 2 ZnMSe 4 (M = Ge, Sn), [ 12 ] Li 2 CdMSe 4 (M = Ge, Sn), [ 13 ] Li 2 In 2 MSe 6 (M = Si, Ge), [ 14 ] Na 4 MgM 2 Se 6 (M = Si, Ge), [ 15 ] BaGa 2 MSe 6 (M = Si, Ge), [ 16 ] γ ‐NaAsSe 2 , [ 17 ] Na 6 MSe 4 (M = Zn, Cd), [ 18 ] CsM 3 Se 6 (M = Ga/Sn, In/Sn), [ 19 ] and AgLiGa 2 Se 4 [ 20 ] have been designed and synthesized successfully. However, to enhance the LIDT, the band gaps in selenides are still highly expected to be further improved.…”
Section: Introductionmentioning
confidence: 99%